Perception of Students on Online Assessment: A Descriptive Study among Medical Undergraduates at Basic Sciences - Maharjan, B. R.; Devbhandari, R. P.; Pradhan, P.; Byanju, J.; Aryal, S. (Kathmandu University Medical Journal, 2021)
Background Assessment drives learning. Student assessment cannot be neglected in the long ongoing online learning during COVID-19 pandemic to motivate and assess students’ learning. Hence Patan Academy of Health Sciences (PAHS) conducted online assessment to medical undergraduates amidst limitations. Objective To measure the perception of online assessment of students which will provide applicable insights for the further improvement. Method This is a single center, cross-sectional and descriptive study. A Google form containing a semi-structured questionnaire was sent to MBBS students of Basic Science at PAHS who attended online classes and online examination. The responses from close ended questions expressed in percentage and Chi-square test was used to find the association. Open ended questions were analyzed using Braun and Clarke’s thematic analysis. Result Of 118 students that responded, 75% passed the online examination. A majority of students (73%) stated that online exam motivated them in learning process and it could be a good alternative during pandemic time. However the most of students (56%) were unsatisfied with the modality of online assessment and reasons that they mentioned were technical problems (89%), inadequate online proctoring (77%), insufficient examination time (58%), lack of orientation to exam, lack of computer skills. Technical problem was worse in rural areas. Conclusion Even though online assessment motivated students’ learning during online classes, a large number of students were unsatisfied with assessment modality.